2019
DOI: 10.3390/ijms21010153
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Copper- and Zinc- Binding Metallothioneins from the Marine Alga Ulva compressa (Chlorophyta)

Abstract: In this work, transcripts encoding three metallothioneins from Ulva compressa (UcMTs) were amplified: The 5′and 3′ UTRs by RACE-PCR, and the open reading frames (ORFs) by PCR. Transcripts encoding UcMT1.1 (Crassostrea-like), UcMT2 (Mytilus-like), and UcMT3 (Dreissena-like) showed a 5′UTR of 61, 71, and 65 nucleotides and a 3′UTR of 418, 235, and 193 nucleotides, respectively. UcMT1.1 ORF encodes a protein of 81 amino acids (MW 8.2 KDa) with 25 cysteines (29.4%), arranged as three motifs CC and nine motifs CXC;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…The levels of transcripts encoding MTs, antioxidant enzymes, and enzymes involved in ASC and GSH synthesis, were increased in the alga exposed to copper excess [16]. Finally, transcripts encoding three MTs, MT1, MT2 and MT3, were cloned from U. compressa and their overexpression in bacteria allowed the accumulation of copper and zinc in vivo [17]. Thus, U. compressa may accumulate copper in its tissue through the binding of copper ions to GSH, PCs and MTs and this alga could represent a useful tool for phycoremediation of seawater contaminated with heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of transcripts encoding MTs, antioxidant enzymes, and enzymes involved in ASC and GSH synthesis, were increased in the alga exposed to copper excess [16]. Finally, transcripts encoding three MTs, MT1, MT2 and MT3, were cloned from U. compressa and their overexpression in bacteria allowed the accumulation of copper and zinc in vivo [17]. Thus, U. compressa may accumulate copper in its tissue through the binding of copper ions to GSH, PCs and MTs and this alga could represent a useful tool for phycoremediation of seawater contaminated with heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of Fucus MT in Escherichia coli allowed the accumulation of arsenite and arsenate, but not cadmium, zinc, or lead [34]. It was recently shown that three MTs of the green alga U. compressa allowed the accumulation of copper and zinc in E. coli [25]. Thus, the excess of copper and other heavy metals induced the synthesis of PCs and MTs in marine macroalgae allowing heavy metal accumulation.…”
Section: Mechanisms Of Copper Accumulation In Plants and Marine Macromentioning
confidence: 99%
“…Surprisingly, the UcMTs' amino acid sequences were not closely related with MTs from red or brown marine macroalgae. The open reading frames (ORFs) of UcMTs were cloned in an expression vector that allow the synthesis of a fusion protein containing in N-terminal position a GST of the flatworm Shistosoma japonicum followed by UcMT [25]. Importantly, S. japonicum's GST contains a single cysteine in its amino acid sequence and, thus, is unable to bind heavy metal ions.…”
Section: Mechanisms Of Copper Accumulation In the Marine Macroalga Umentioning
confidence: 99%
See 2 more Smart Citations